THE OPERATIONAL MODE OF OPTICAL MICROSCOPE APPLYING PHOTONIC JET MICROSCOPY - Andri Abdurrochman; Julian Akmal S; Ela Septianingsih; Intan F. Amatillah; L. Safriani (Spektra: Jurnal Fisika dan Aplikasinya, 2021)
The previous experimental research on microsphere parameters applying photonic jet microscopy in free space revealed if the relative indexes come near to two, it needs larger microspheres. It also means if the relative indexes come near to one, it needs smaller microsphere. In addition to these premises, the mode of ordinary optical microscope introducing photonic jet microscopy in its operation must be taken into account. That includes the light source or filter, and the fluidic environment - free space or immersion oil. These additional modes are predicted in two dimensional finite element method calculation. Which leads to more practical use of photonic jet microscopy in the near future.